A PENDIDIKAN MODEL TEMATIK DAN INTEGRATIF PERSPEKTIF ISLAM - Mohammad Zakki; Nanda Saputra (Indra Institute Research & Publication, 2022)
Education is an institution that has the power to create human beings who have noble character, broad-minded in scientific disciplines and believe in accordance with their religion and the ability to carry out His commands and prohibitions. Many phenomena in society are still far from the noble ideals of education and or the main mission of existing educational institutions. The injustice of the bureaucratic players or the elite class against the rights that should be owned by the community, the rape of democratic values ​​and criminal acts that are often carried out by today's youth. The aims of this study: (1) to determine the decadence factors of character education values; (2) knowing the importance of integrating material with attitudes towards students, and (3) knowing the roles, responsibilities and emotional relationships of educators, students and families. The type of research used is qualitative research with a literature review approach, namely comparing several concepts and then taking the common thread. While the results of this study are the low support and examples of family attitudes towards children in daily life while at home, character education is in accordance with the concept of the Qur'an which unites theory with implementation, science with faith and textual with contextual, and teachers at school are educators who are professional while both people or families are natural educators in the household where both have roles and responsibilities to students.